Domestic and international issues in the regulation of civil and military equipment (Academic Journal of Internal Affairs, 2021)
The legal regulation of civil and military equipment is marginal, may seem to be an area with no particular importance. However, this regulation can be considered sector-significant, especially within individual sectors, such as organizations dealing with civilian firearms, their accessories and military equipment. At the same time, the regulation forms a comprehensive set of provisions consisting of several European Union and Hungarian legal acts with a relatively narrow legal application practice, which so far has not yet been examined in detail in Hungary.
Keywords: civilian firearms; military technology; legislation; legal interpretation